Assessment of the Fatigue Behavior of Wings with Distributed Propulsion - Lukas Kettenhofen; Martin Schubert; Kai-Uwe Schröder (Engineering Proceedings, 2025)
The integration of distributed electric propulsion into a wing significantly alters the dynamic behavior of the wing. Consequently, the loads on the wing structure in service, in particular upon transient gust and landing impact loads, change substantially compared with conventional aircrafts with main engines mounted on the inner wing. As this might significantly increase the stress levels and number of load cycles, this paper assesses the impact of wing-integrated distributed propulsion on the fatigue behavior of the wing structure. This assessment is conducted based on a retrofit scenario of a conventional 19-seater commuter aircraft of the CS-23 category retrofitted with distributed electric propulsion. The wing structure is idealized with beam elements. Static and dynamic response analyses followed by stress analyses are conducted for typical load cases occurring during operation of the aircraft. The fatigue analysis is carried out based on the safe life approach. This study concludes that the integration of distributed electric propulsion has a substantial impact on the fatigue behavior of the wing. A significant increase in fatigue damage for the electric configurations compared with the conventional configuration is observed, in particular in the outer wing area. The increased damage accumulation is a result of the higher stress amplitudes and the longer decay duration of the structural vibrations due to gusts. The results suggest that adjustments to the structural design and maintenance procedures of future electric aircrafts may be necessary.